(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Consumers are the decisive factors in any economic system. Due to technical development and due to the influence of Mass Media, there is an increased health consciousness in the society. Consumers always search for cheap and best and at the same time nutrients rich health products in the market. Various analytical survey about the consumer behavior of the Thanjavur locality prove the mentality of consumers, that they need health drinks at an affordable price. The young generation purchases health products only after detailed study of nutrients contents and the price of each products, and they compare quality products in the market. Moreover there is a great competition in the market between the different companies and their products like Horlicks, Boost, Complan, Bournvita, Milo etc. Different aspects affect a consumer in their choice. It may include, social factors and personal factors and their believes. Media and advertisements also affect the decisive factor and most of the consumers depend on brand loyalty, as well as gifts offered by manufactures. So manufactures should produce good quality health products enriched with nutrients at an affordable price.